2019
DOI: 10.1080/20013078.2019.1635420
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial protein enriched extracellular vesicles discovered in human melanoma tissues can be detected in patient plasma

Abstract: Lötvall (2019) Mitochondrial protein enriched extracellular vesicles discovered in human melanoma tissues can be detected in patient plasma,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(147 citation statements)
references
References 51 publications
9
138
0
Order By: Relevance
“…EVs from patients with HTR disease contain full mitochondrial genome that might have been transferred to HTS/HTD cells to sustain oxidative phosphorylation, an exit from dormancy and the development of HTR disease (111). Additional findings show that EVs from melanoma, ovarian and breast cancer tissues contain mitochondrial membrane proteins and active mitochondrial enzymes that are not detected in healthy controls (112), thus corroborating the hypothesis that energy metabolism reprogramming in cancer cells may occur also via EVs.…”
Section: Implication Of Extracellular Vesicles and Damage-associated supporting
confidence: 64%
“…EVs from patients with HTR disease contain full mitochondrial genome that might have been transferred to HTS/HTD cells to sustain oxidative phosphorylation, an exit from dormancy and the development of HTR disease (111). Additional findings show that EVs from melanoma, ovarian and breast cancer tissues contain mitochondrial membrane proteins and active mitochondrial enzymes that are not detected in healthy controls (112), thus corroborating the hypothesis that energy metabolism reprogramming in cancer cells may occur also via EVs.…”
Section: Implication Of Extracellular Vesicles and Damage-associated supporting
confidence: 64%
“…More recently, Cresticelli et al [42] performed proteomic analysis of small and large EVs isolated from melanoma tumors and confirmed that metastatic melanoma tissues contain a mixture of EVs derived from tumor and immune cells. The same group also showed that two mitochondrial inner membrane proteins: cytochrome c oxidase subunit 2 (MT-CO2) and cytochrome c oxidase subunit 6C (COX6c) are enriched in the plasma of melanoma patients as well as in tumor tissues-derived EVs compared to healthy controls [43]. Studies using human tumor tissues are particularly valuable, since they fully reflect the complexity and cellular interactions present within the tumor microenvironment.…”
Section: Melanoma-derived Ectosomes As a Source Of Potential Disease mentioning
confidence: 99%
“…In 2017, Vella et al used frozen human brain tissue to study EVs [31]. More recently, Jang et al studied EVs from metastatic human melanoma and Jingushi et al isolated EVs from human kidney tumors [21,32]. Although Jingushi et al reported successful EV isolation from RCC, we found it necessary to optimize available protocols to reduce non-EV contaminants to acceptable levels.…”
Section: Discussionmentioning
confidence: 95%
“…We have adapted an EV isolation method employed for metastatic melanoma and optimized it to isolate EVs from kidney tumor and normal kidney tissue [21]. This protocol demonstrates a high EV yield that is sufficient for downstream analysis.…”
Section: Introductionmentioning
confidence: 99%